Technology and science education: Starting points, research programs, and trends - Linn, Marcia (International Journal of Science Education, 2003)
Over the past 25 years, information and communication technologies have had a convoluted but ultimately advantageous impact on science teaching and learning. To highlight the past, present, and future of technology in science education, this paper explores the trajectories in five areas: science texts and lectures; science discussions and collaboration; data collection and representation; science visualization; and science simulation and modeling. These trajectories reflect two overall trends in technological advance. First, designers have tailored general tools to specific disciplines, offering users features specific to the topic or task. For example, developers target visualization tools to molecules, crystals, earth structures, or chemical reactions. Second, new technologies generally support user customization, enabling individuals to personalize their modeling tool, Internet portal, or discussion board. In science education, designers have tailored instructional resources based on advances in understanding of the learner. More recently, designers have created ways for teachers and students to customize learning tools to specific courses, geological formations, interests, or learning preferences.